2005
DOI: 10.1108/17439130510600802
|View full text |Cite
|
Sign up to set email alerts
|

Underpricing, share retention, and the IPO aftermarket liquidity

Abstract: Purpose -To test the effects of underpricing and share retention (i.e. the proportion of shares retained by the pre-initial-public-offering (IPO) owners) on IPO aftermarket liquidity. Design/methodology/approach -Uses both percentage spread and turnover ratio to measure liquidity. The percentage spread is the quoted bid-ask spread divided by the quoted midpoint and measures the trading cost relative to share price. Turnover ratio is the daily trading volume divided by the number of shares offered and measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 51 publications
4
26
0
10
Order By: Relevance
“…The ultimate relationship between share retention and liquidity will depend on whether the share-fl oating effect dominates the signalling effect or vice versa. Consistent with signalling theory, Li et al (2005) found pre-IPO owners' retention to be positively related to trading turnover and negatively related to bid-ask spread. They concluded that high retention rates attract more trades, provide quality assurance, and improve IPO aftermarket liquidity.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…The ultimate relationship between share retention and liquidity will depend on whether the share-fl oating effect dominates the signalling effect or vice versa. Consistent with signalling theory, Li et al (2005) found pre-IPO owners' retention to be positively related to trading turnover and negatively related to bid-ask spread. They concluded that high retention rates attract more trades, provide quality assurance, and improve IPO aftermarket liquidity.…”
Section: Introductionsupporting
confidence: 70%
“…While most of the research on IPOs has focused on explaining the underpricing phenomenon, few studies have investigated the determinants of after-market liquidity (see Pham et al, 2003;Corwin et al, 2004;Li et al, 2005;Zheng et al, 2005;Ellul and Pagano, 2006;and Zheng and Li, 2008). For this reason we focus our attention on liquidity for the post-listing period.…”
Section: Ipo Characteristics and Influence On Liquiditymentioning
confidence: 99%
See 2 more Smart Citations
“…On average, underpriced IPOs exhibit higher aftermarket trading activity than overpriced IPOs (Miller and Reilly, 1987;Hanley, 1993;Schultz and Zaman, 1994;Reese, 1998;Hahn and Ligon, 2006;Li and Zheng, 2008). A higher level of underpricing leads not only to increased trading turnover but also to lower bid-ask spreads (Pham, Kalev, and Steen, 2003;Li, Zheng, and Melancon, 2005) and lower adverse selection costs (Li, McInish, and Wongchoti, 2005). 1 However, apart from Pham et al (2003), no literature exists on how this positive link between initial underpricing and liquidity actually is formed.…”
Section: Introductionmentioning
confidence: 99%